2003
DOI: 10.1016/s0009-8981(03)00005-6
|View full text |Cite
|
Sign up to set email alerts
|

Soluble transferrin receptor for the evaluation of erythropoiesis and iron status

Abstract: Iron transport in the plasma is carried out by transferrin, which donates iron to cells through its interaction with a specific membrane receptor, the transferrin receptor (TfR). A soluble form of the TfR (sTfR) has been identified in animal and human serum. Soluble TfR is a truncated monomer of tissue receptor, lacking its first 100 amino acids, which circulates in the form of a complex of transferrin and its receptor. The erythroblasts rather than reticulocytes are the main source of serum sTfR. Serum sTfR l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
321
2
38

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 398 publications
(381 citation statements)
references
References 122 publications
20
321
2
38
Order By: Relevance
“…Prior studies have suggested that the sTfR Index may improve the ability to accurately classify anemia in diseases with active inflammation [5,[15][16][17][18]. However, these studies involved single institutions with a limited number of subjects reflecting the specialized patient population at that center, which can introduce possible bias in study outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies have suggested that the sTfR Index may improve the ability to accurately classify anemia in diseases with active inflammation [5,[15][16][17][18]. However, these studies involved single institutions with a limited number of subjects reflecting the specialized patient population at that center, which can introduce possible bias in study outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Calculating the sTfR/log ferritin index (sTfR Index) from these two measures provides an estimate of body iron over a wide range of normal and depleted iron stores [11,15]. The sTfR Index thus takes advantage of the reciprocal relationship between two variables influenced by iron deficiency, an increase in sTfR and a decrease in the ferritin concentration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…STR levels were significantly higher in the high-erythroid-activity group (94 ± 18 nmol/l) compared with the control group (34.05 nmol/l; P < 0.001), but the low-erythroid activity group had similar STR levels as the control group (35.29 ± 17.09 nmol/l; NS). In the absence of iron deficiency, as manifested by the elevated serum ferritin levels, the high STR values reflected high bone marrow erythroid activity [16].…”
Section: Hematological Parametersmentioning
confidence: 99%
“…It is increased not only in ID, but also in diseases with increased erythropoesis (2,7,8). The use of sTfR in lymphoproliferative disorders is particularly tricky, especially in patients with chronic lymphocytic leukemia (CLL).…”
Section: Introductionmentioning
confidence: 99%